Dry-method electrode binder, dry-method electrode, preparation method of dry-method electrode and battery
By using gluten as a binder, the problem of the need for shear force of the binder in the preparation of existing dry electrodes is solved, and the preparation of dry electrodes without shear bonding is realized, reducing costs and environmental pollution, and improving electrochemical performance.
Patent Information
- Application Number
- CN202410579998.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-11
- Publication Date
- 2025-03-07
AI Technical Summary
In the existing dry electrode preparation process, the commonly used binder polytetrafluoroethylene (PTFE) requires shear force to exert the bonding effect, which limits the development of dry electrodes.
Gluten powder is used as the binder for the dry electrode, and the dry electrode is prepared by mixing the battery active material, conductive agent and gluten powder evenly, adding deionized water/ethanol mixed solution, coating it on the current collector and drying.
It realizes dry electrode preparation that can be effectively bonded without shear force, reduces battery manufacturing costs, reduces the use of organic solvents, reduces environmental pollution problems, and improves electrochemical performance.
Smart Images

Figure CN119581559A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of battery manufacturing, and in particular relates to the manufacturing of dry electrodes and a binder used in the manufacturing process of dry electrodes. Background Art
[0002] Secondary batteries are a type of battery with charge and discharge cycle capabilities. They can be used repeatedly and are an important energy storage solution for many modern electronic devices and vehicles. In the positive and negative electrodes of secondary batteries, binders play an important role as key components. Binders play an adhesive role between the positive and negative active materials and the electrode current collectors, ensuring that the active materials are closely attached to the surface of the electrode current collectors, thereby ensuring the stability and cycle performance of the electrodes. The electrode preparation process currently widely used is wet coating, in which PVDF is mainly used as a binder for the positive electrode and CMC is used as a binder for the negative electrode. There are many disadvantages in the wet coating process, including the use of a large amount of organic solvents or aqueous solutions that may cause environmental problems, the drying of electrode sheets requires a lot of energy for solvent evaporation and waste liquid treatment, and the need to wait for solvent evaporation, resulting in relatively slow production speeds. In contrast, it is more convenient to prepare electrode sheets using a dry process. The dry process can better meet the needs of large-scale, efficient, and low-cost production, and help promote the continuous advancement and application of battery technology. At present, the most commonly used dry binder is polytetrafluoroethylene (PTFE), which produces a bonding effect under high shear force and is suitable for various positive and negative electrode materials. However, PTFE requires shear force to exert its adhesiveness, which restricts the development of dry electrodes. Summary of the invention
[0003] The first object of the present invention is to provide a dry electrode binder.
[0004] The second object of the present invention is to provide a method for preparing a dry electrode.
[0005] The third object of the present invention is to provide a dry electrode.
[0006] A fourth object of the present invention is to provide a battery.
[0007] To achieve the above objectives, the present invention provides the following specific technical solutions.
[0008] Firstly, the present invention provides application of gluten powder as a dry electrode binder.
[0009] Secondly, the present invention provides a method for preparing a dry electrode, comprising the following steps: The battery active material, the conductive agent and the gluten powder are uniformly mixed to obtain a dry mix; Adding a deionized water / ethanol mixed solution to the dry blend, stirring thoroughly, to obtain a slurry; The slurry is coated on a current collector, and then the current collector is dried to obtain a dry electrode.
[0010] In the present invention, the battery active material is one of lithium battery positive electrode material, lithium battery negative electrode material, sodium battery positive electrode material, sodium battery negative electrode material, potassium battery positive electrode material, potassium battery negative electrode material, magnesium battery positive electrode material, magnesium battery negative electrode material, calcium battery positive electrode material, and calcium battery negative electrode material.
[0011] Furthermore, the lithium battery positive electrode material includes but is not limited to at least one of lithium iron phosphate, lithium manganese oxide, lithium iron manganese phosphate, lithium cobalt oxide, and lithium nickel cobalt manganese oxide; the lithium battery negative electrode material includes but is not limited to one of graphite, silicon carbon, and pure silicon; the sodium battery positive electrode material includes but is not limited to at least one of sodium vanadium phosphate, sodium vanadium fluorophosphate, and sodium nickel manganese oxide; the sodium battery negative electrode material includes but is not limited to hard carbon.
[0012] In a further preferred embodiment, the conductive agent is at least one of carbon black, conductive graphite, acetylene black, Super P, graphene, carbon nanotubes, Ketjen black, and carbon fiber.
[0013] In a further preferred embodiment, the mass ratio of the battery active material, the conductive agent and the gluten powder is (6.5-9.5): (0.25-1.5): (0.25-2).
[0014] In a further preferred embodiment, the mass concentration of ethanol in the deionized water / ethanol mixed solution is 3-40wt%.
[0015] In a further preferred embodiment, the amount of the deionized water / ethanol mixed solution added is 2-20 wt % of the dry mix.
[0016] In a further preferred embodiment, the current collector includes but is not limited to aluminum foil, carbon-coated aluminum foil, stainless steel mesh, titanium foil, copper foil, and carbon-coated copper foil.
[0017] In a further preferred embodiment, the drying temperature is 30-60°C.
[0018] Based on the same inventive concept, the present invention provides a dry electrode prepared by the above preparation method, and a battery comprising the dry electrode.
[0019] Compared with the prior art, one or more of the above technical solutions of the present invention can achieve at least one of the following beneficial effects: The invention opens up a new application field of gluten powder.
[0020] The present invention adopts gluten powder as a binder for dry-process electrodes, which has low cost, wide sources and strong universality.
[0021] The present invention adopts gluten powder as a binder of dry electrode to grow and manufacture battery pole pieces, thereby reducing the cost of battery manufacturing, reducing the use of organic solvents, and reducing environmental pollution problems.
[0022] After the battery electrodes using gluten powder as a binder are assembled into batteries, the electrochemical performance is good and has strong commercial prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is the electrochemical cycle performance diagram of the battery assembled with the electrodes prepared in Example 1.
[0024] Figure 2 This is the electrochemical cycle performance diagram of the battery assembled with the electrodes prepared in Example 2.
[0025] Figure 3 This is the electrochemical cycle performance diagram of the battery assembled with the electrodes prepared in Example 3.
[0026] Figure 4 This is the electrochemical cycle performance diagram of the battery assembled with the electrodes prepared in Example 4.
[0027] Figure 5 This is the electrochemical cycle performance diagram of the battery assembled with the electrodes prepared in Example 5.
[0028] Figure 6 This is the electrochemical cycle performance diagram of the battery assembled with the electrodes prepared in Example 6.
[0029] Figure 7 This is the electrochemical cycle performance diagram of the battery assembled with the electrodes prepared in Example 7.
[0030] Figure 8 This is the electrochemical cycle performance diagram of the battery assembled with the electrodes prepared in Example 8. DETAILED DESCRIPTION
[0031] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and meticulously below in conjunction with the accompanying drawings and preferred embodiments of the present invention, but the protection scope of the present invention is not limited to the following specific embodiments.
[0032] Unless otherwise defined, all the professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.
[0033] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.
[0034] Example 1 8 g of lithium iron phosphate, a battery active material, 0.5 g of acetylene black, a conductive agent, and 0.5 g of gluten powder were mixed evenly to obtain 9 g of dry mixed material; Add 1 g of deionized water / ethanol mixed solution (ethanol concentration is 10 wt%) to 9 g of dry blend, stir thoroughly to obtain wet material; The wet material was pressed onto an aluminum foil current collector using a double-roller machine, and then the current collector was dried at 60°C to obtain a dry electrode.
[0035] Example 2 6.5 g of lithium cobalt oxide, a battery active material, 0.5 g of a conductive agent Super P, and 0.5 g of gluten powder were mixed evenly to obtain 7.5 g of a dry blend; Add 1.5 g of deionized water / ethanol mixed solution (the concentration of the ethanol solution is 20 wt%) to 7.5 g of the dry blend, stir thoroughly, and obtain a wet material; The wet material was pressed onto an aluminum foil current collector using a double-roller press, and then the current collector was dried at 50°C to obtain a dry electrode.
[0036] Example 3 7.5 g of battery active material lithium nickel cobalt manganese oxide (NCM622), 1.5 g of conductive agent acetylene black, and 2 g of gluten powder were mixed evenly to obtain 11 g of dry mix; 0.22 g of a deionized water / ethanol mixed solution (ethanol concentration is 10 wt%) was added to 11 g of the dry blend and stirred thoroughly to obtain a wet material; The wet material was pressed onto an aluminum foil current collector using a double-roller press, and then the current collector was dried at 30°C to obtain a dry electrode.
[0037] Example 4 7.5 g of battery active material graphite, 0.25 g of conductive agent carbon black, and 0.25 g of gluten powder were mixed evenly to obtain 8 g of dry blend; 1.6 g of deionized water / ethanol mixed solution (ethanol concentration is 3 wt%) was added to 8 g of the dry blend and stirred thoroughly to obtain a slurry; The wet material was pressed onto a copper foil current collector using a double-roller machine, and then the current collector was dried at 40°C to obtain a dry electrode.
[0038] Example 5 7 g of battery active material silicon-carbon negative electrode (20% silicon content), 0.5 g of conductive agent acetylene black, and 1 g of gluten powder were mixed evenly to obtain 8.5 g of dry mixed material; Add 1 g of deionized water / ethanol mixed solution (ethanol concentration is 10 wt%) to 8.5 g of dry blend, stir thoroughly to obtain wet material; The wet material was pressed onto a copper foil current collector using a double-roller machine, and then the current collector was dried at 60° C. to obtain a dry electrode.
[0039] Example 6 8 g of the battery active material sodium vanadium phosphate, 1 g of the conductive agent Super P, and 1.5 g of gluten powder were mixed evenly to obtain 10.5 g of dry mix; Add 3 ml of deionized water / ethanol mixed solution (ethanol concentration is 30 wt%) to 10.5 g of the dry blend, stir thoroughly, and obtain a slurry; The wet material was pressed onto a carbon-coated aluminum foil current collector using a double-roller press, and then the current collector was dried at 50°C to obtain a dry electrode.
[0040] Example 7 8.5 g of battery active material sodium vanadium fluorophosphate, 1 g of conductive agent Ketjen black, and 0.5 g of gluten powder were mixed evenly to obtain 10 g of dry mix; Add 2 g of deionized water / ethanol mixed solution (ethanol concentration is 40 wt%) to 10 g of the dry blend, stir thoroughly, and obtain a slurry; The wet material was pressed onto a carbon-coated aluminum foil current collector using a double-roller press, and then the current collector was dried at 40°C to obtain a dry electrode.
[0041] Example 8 9.5 g of hard carbon as a battery active material, 1.0 g of graphene as a conductive agent, and 1.0 g of gluten powder were mixed evenly to obtain 11.5 g of a dry blend; Add 2 g of deionized water / ethanol mixed solution (ethanol concentration is 15 wt%) to 11.5 g of dry blend, stir thoroughly to obtain wet material; The wet material was pressed onto a carbon-coated copper foil current collector using a double-roller press, and then the current collector was dried at 30°C to obtain a dry electrode.
[0042] The dry electrodes obtained in the above embodiment are assembled into a battery in the following manner: 1. Lithium battery: The assembly method of lithium battery positive and negative electrode materials (lithium iron phosphate, lithium cobalt oxide, nickel cobalt manganese oxide NCM622, graphite, silicon carbon negative electrode) is similar. The electrodes made by dry method are combined with lithium metal in a glove box with water and oxygen content below 0.1ppm for half-cell assembly. 1M LiPF 6 Commercial electrolyte with EC / EMC / DMC solvent volume ratio of 1:1:1.
[0043] The half-cell assembled with electrodes obtained in Example 1: The test procedure is a charge-discharge voltage range of 2-3.7 V and a current of 1 C. The cycle performance obtained by the test is shown in Figure 1 After 50 cycles, the battery still has 144.86 mAh g -1 The specific capacity of the battery is as high as 95.79%.
[0044] The half-cell assembled with electrodes obtained in Example 2: The test procedure is a charge-discharge voltage range of 3-4.4 V and a current of 1 C. The cycle performance obtained by the test is shown in Figure 2 After 100 cycles, the battery still has 154.31 mAh g -1 The specific capacity retention rate is as high as 96.29%.
[0045] The half-cell assembled with electrodes obtained in Example 3: The test procedure is a charge and discharge voltage range of 2.8-4.4 V and a current of 1C. The cycle performance obtained by the test is shown in Figure 3 After 100 cycles, the battery still has 163.58 mAh g -1 The specific capacity retention rate is as high as 93.23%.
[0046] The electrode-assembled half-cell obtained in Example 4: The test procedure is 0.01-2V charge and discharge voltage range and 0.5Ag -1 The current of the test results is shown in Figure 4 After 300 cycles, the battery capacity increased from 270.28 mAh g -1 Change to 243.37 mAh g -1 The specific capacity retention rate is as high as 90.04%.
[0047] The electrode-assembled half-cell obtained in Example 5: The test procedure is 0.01-2 V charge and discharge voltage range and 0.5A g -1 The current of the test results is shown in Figure 5 After 100 cycles, the battery capacity increased from 480.49 mAh g -1 Change to 465.64 mAh g -1 The specific capacity retention rate is as high as 96.91%.
[0048] 2. Sodium electricity: The assembly method of sodium positive and negative electrode materials (sodium vanadium phosphate, sodium vanadium fluorophosphate, and hard carbon negative electrode) is similar. The electrode prepared by the dry method is combined with sodium metal in a glove box with a water and oxygen content of less than 0.1ppm to assemble a half-cell. 1M NaClO 4 The commercial electrolyte was prepared with a solvent volume ratio of EC / PC of 1:1. After assembly, the battery was left to stand for 12 hours before the cycle performance test.
[0049] The half-cell assembled with electrodes obtained in Example 6: The test procedure is a charge-discharge voltage range of 2-3.7 V and a current of 2 C. The cycle performance obtained by the test is shown in Figure 6 After 300 cycles, the battery capacity increased from 111.08 mAh g -1 Change to 105.10mAh g -1The specific capacity retention rate is as high as 94.62%.
[0050] The half-cell assembled with electrodes obtained in Example 7: The test procedure is a charge-discharge voltage range of 2-4.2 V and a current of 2 C. The cycle performance obtained by the test is shown in Figure 7 After 500 cycles, the battery capacity increased from 123.45 mAh g -1 Change to 113.47mAh g -1 The specific capacity retention rate is as high as 91.91%.
[0051] The electrode-assembled half-cell obtained in Example 8: The test procedure is 0.01-2 V charge and discharge voltage range and 1 Ag -1 The current of the test results is shown in Figure 8 After 300 cycles, the battery capacity increased from 294.56 mAh g -1 Change to 291.57mAh g -1 The specific capacity retention rate is as high as 98.98%.
[0052] From the above test results, it is not difficult to see that the battery has excellent cycle performance after the prepared electrodes are assembled into a battery using only gluten powder as a binder.
[0053] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. Application of gluten powder as dry electrode binder.
2. A method for preparing a dry electrode, characterized in that: The following steps are involved: The battery active material, the conductive agent and the gluten powder are uniformly mixed to obtain a dry mix; Adding a deionized water / ethanol mixed solution to the dry blend, stirring thoroughly, to obtain a slurry; The slurry is coated on a current collector, and then the current collector is dried to obtain a dry electrode.
3. The preparation method according to claim 2, characterized in that: The conductive agent is at least one of carbon black, conductive graphite, acetylene black, Super P, graphene, carbon nanotubes, Ketjen black, and carbon fiber.
4. The preparation method according to claim 2 or 3, characterized in that: The mass ratio of the battery active material, the conductive agent and the gluten powder is (6.5-9.5): (0.25-1.5): (0.25-2).
5. The preparation method according to claim 2 or 3, characterized in that: The mass concentration of ethanol in the deionized water / ethanol mixed solution is 3-40wt%.
6. The preparation method according to claim 5, characterized in that: The added amount of the deionized water / ethanol mixed solution is 2-20wt% of the dry blend.
7. The preparation method according to claim 2 or 3, characterized in that: The current collector includes but is not limited to aluminum foil, carbon-coated aluminum foil, stainless steel mesh, titanium foil, copper foil, and carbon-coated copper foil.
8. The preparation method according to claim 2 or 3, characterized in that: The drying temperature is 30-60°C.
9. A dry electrode, characterized in that: It is prepared by the preparation method according to any one of claims 2 to 8.
10. A battery, characterized in that: Comprising the dry electrode as described in claim 9.
Citation Information
Patent Citations
Electrode for lithium ion secondary battery and lithium ion secondary battery
CN101847709A
Dry preparation method of lithium battery electrode
CN113793917A
Application of composite material as active material of positive electrode and super-capacitor carbon dioxide adsorption energy storage device
CN117650015A
Binder, electrode and electrochemical capacitor
JP2016066755A
Method of producing electrode
JP2017111970A